Tinjauan Sistem Keamanan Rekam Medis Elektronik di Rumah Sakit Al Dr. Mintohardjo Jakarta - Aldo Rizky Mahendra; Siswati Siswati; Dina Sonia; Muhammad Fuad Iqbal (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the security concerns surrounding electronic medical records (EMR) at AL Dr. Mintohardjo Hospital, which currently uses a hybrid system combining both manual and electronic methods. Despite the benefits of EMR in improving efficiency and accuracy, challenges persist in transitioning to a fully digital system. The research identifies key issues such as data entry errors and insufficient cybersecurity training for medical record staff. Data was collected through interviews and participant observation with administrative, medical, and IT department members. Although the hospital has established Standard Operating Procedures (SOP) for EMR security, the study finds that these procedures are not effectively implemented. Security measures such as access control and user authentication have been put in place to protect patient data, but vulnerabilities remain, such as excessive access by administrators and infrequent password updates by users. Additionally, data entry mistakes can negatively impact patient care, and concerns about unstable internet connections and reliance on a single resource persist. Despite the hospital's security efforts, including audit trails and firewalls, the study emphasizes the need for better staff training and enhanced procedures to further safeguard the confidentiality, integrity, and availability of EMR data.